A guide to data breaches and indemnity issues. (2nd June 2022) - McGuire, Dawn
Abstract : Indemnity issues surrounding data breaches can be complex and it is important that practices are aware of the requirements. Dr Dawn McGuire, Medicolegal Consultant at Medical Protection, explains